THE PRINCIPAL'S LEADERSHIP ROLE IN DEVELOPING RELIGIOUS CULTURE AT SCHOOL - Faiz, M. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out and describe the leadership role of the principal in developing religious culture at SMPN 1 Wringan Bondowoso for the 2022-2023 academic year. The research method used is a qualitative approach that produces naturalistic data in the form of natural explanations. The data collection method uses observation, interviews and documentation, while the analysis method uses interactive models in the form of data collection, data reduction, data presentation and conclusions. And obtain the validity of the data using the validity of the data with the source trianggulation technique. The results of this study show that the role of the principal in developing religious culture at SMPN 1 Wringan by carrying out education in the academic and nonacademic fields by supporting Islamic values and prioritizing akhlakul karimah. Although it is not an Islamic school, it does not change the context of religious education carried out by SMPN 1 Wringan such as habituation to recite before lessons begin, Friday charity, congregational dhuhur prayers, and commemoration of Islamic holidays